2020
DOI: 10.1186/s13287-020-01807-3
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of mesenchymal stem cells against Staphylococcus aureus

Abstract: Introduction: There have been limited advances in the treatment of bone and joint infections, which currently involves a combination of surgery and antibiotic administration. There is a timely need in orthopedics to develop more effective and less invasive forms of antimicrobial prophylaxis and treatment. The antibacterial effect of adult tissue-derived mesenchymal stem cells (MSCs) has recently been investigated against Escherichia coli and Staphylococcus aureus. The main mechanism of action is postulated to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 66 publications
1
30
0
1
Order By: Relevance
“…Thus, they might act directly through the secretion of antimicrobial peptides, which are evolutionarily conserved small effector molecules (10–150 amino acids) found in organisms ranging from prokaryotes to humans [ 75 ]. These peptides include cathelicidin, defensins, cystatin C, elafin, and lipocalin 2 [ 76 ]. They mediate antimicrobial cell killing, which occurs by disrupting membrane integrity; inhibiting protein, DNA, or RNA synthesis; and interacting with certain intracellular targets [ 77 ].…”
Section: Msc: Nomenclature Properties Heterogeneity and Realitymentioning
confidence: 99%
“…Thus, they might act directly through the secretion of antimicrobial peptides, which are evolutionarily conserved small effector molecules (10–150 amino acids) found in organisms ranging from prokaryotes to humans [ 75 ]. These peptides include cathelicidin, defensins, cystatin C, elafin, and lipocalin 2 [ 76 ]. They mediate antimicrobial cell killing, which occurs by disrupting membrane integrity; inhibiting protein, DNA, or RNA synthesis; and interacting with certain intracellular targets [ 77 ].…”
Section: Msc: Nomenclature Properties Heterogeneity and Realitymentioning
confidence: 99%
“…Exploration of human stem cells has also shown the potential of these cells as anti-staphylococcal therapeutics. Studies have showed that the adipose-derived human mesenchymal stem cells (MSC) significantly inhibited the growth of S. aureus under standard culture conditions with or without the continued presence of adipose stem cells (ASCs) through MSC production of the cationic antimicrobial peptide, LL-37 [ 61 ]. In addition, treatment of ASCs with 1,25(OH)2 vitamin D3 elevated LL-37 expression and enhanced their antimicrobial activity, whereas a vitamin D receptor inhibitor, GW0742, blocked the antimicrobial activity of MSCs [ 61 ].…”
Section: Immune Boosting Strategiesmentioning
confidence: 99%
“…Studies have showed that the adipose-derived human mesenchymal stem cells (MSC) significantly inhibited the growth of S. aureus under standard culture conditions with or without the continued presence of adipose stem cells (ASCs) through MSC production of the cationic antimicrobial peptide, LL-37 [ 61 ]. In addition, treatment of ASCs with 1,25(OH)2 vitamin D3 elevated LL-37 expression and enhanced their antimicrobial activity, whereas a vitamin D receptor inhibitor, GW0742, blocked the antimicrobial activity of MSCs [ 61 ]. When introduced into rats, bone marrow-derived MSCs enhanced bacterial clearance, suppressed the expression of cytokines and chemokines and promoted healing of the wound, in comparison to the fibroblast control groups [ 62 ].…”
Section: Immune Boosting Strategiesmentioning
confidence: 99%
“…A number of preconditioning methods have been employed over the years including hypoxia, serum deprivation, and exposure to antagonistic substances to improve MSCs' ability to differentiate or modulate immune cells. Conditions promoting antimicrobial activity are being examined with exposure to cytokines, target bacteria, bacterial components, vitamins, and antibiotics improving both direct and indirect antimicrobial effects (Gupta et al, 2012;Guerra et al, 2017;Johnson et al, 2017;Cahuascanco et al, 2019;Yagi et al, 2020).…”
Section: Antimicrobial Effect Of Mscsmentioning
confidence: 99%
“…Investigators identified LL-37 activity as crucial to MSC antimicrobial activity in vitro as well as in an in vivo mouse model using human MSCs (Krasnodembskaya et al, 2010). Yagi et al (2020) further found LL-37 activity from adipose-derived MSCs was dependent on 1,25-dihydroxy vitamin D3. 1,25-dihydroxy vitamin D3 supplementation enhanced LL-37 production relative to MSCs under standard culture conditions, whereas treatment with a vitamin D receptor inhibitor nullified the antibacterial response.…”
Section: Direct Mechanisms Of Antimicrobial Effects Of Mscmentioning
confidence: 99%